Returning cycles : contexts for the interpretation of Schubert's impromptus and last sonatas - Fisk, Charles (California studies in 19th century music, 2001)
This compelling investigation of the later music of Franz Schubert explores the rich terrain of Schubert's impromptus and last piano sonatas.